Membangun Disiplin Siswa Melalui Keteladanan dan Pembelajaran Sosial: Pendekatan Teori Sosial Kognitif di Sekolah - Fazli, M.; Nirwana, Herman; N, Neviyarni (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Discipline is an important foundation in shaping students’ character and academic success. This study aims to analyze how teacher role models and social learning can shape student discipline in elementary schools using Albert Bandura’s Social Cognitive Theory approach. This study uses a qualitative method with a case study approach at SD Negeri X. Data were collected through interviews, observations, and documentation. The results of the study indicate that teacher role models in terms of discipline, such as being on time, consistently enforcing rules, and showing empathy, greatly influence student behavior. Social learning such as group discussions, simulations, and self-reflection also help students build self-control and responsibility. The process of modeling, reinforcement, and social observation are the main mechanisms in shaping disciplined behavior. This study emphasizes the importance of the role of teachers as role models and facilitators of social learning in instilling discipline values continuously.